The relationship between the concentrations of some atmospheric pollutants and meteorological parameters - Kizhner, Lubov I. (Proceedings of SPIE)
The correlation between meteorological values and the concentration of impurities in the atmosphere is examined based on hourly observations at the tor station and weather stations of the atmosphere JUC (joint use center) of the IOA SB RAS, in Tomsk for the year 2020. It is shown that there is a reliable statistical relationship between the CO, CO2, O3, and PM10 content and wind speed, air temperature, and atmospheric pressure. There is a closer relationship between the averaged values of meteorological parameters and concentration of impurities with the correlation coefficient for different impurities being 0.6-0.9. Air temperature is of primary importance for air pollution. It was found that the content of the substances under consideration, except for ozone, does not exceed the maximum permissible concentration. The state of the atmosphere is not safe in terms of the ozone content.